Excision of oxidatively damaged DNA bases by the human alpha-hOgg1 protein and the polymorphic alpha-hOgg1(Ser326Cys) protein which is frequently found in human populations. - Dherin, C (1999)
We have investigated the substrate specificity of the major nuclear form of the human Ogg1 protein, referred as alpha-hOgg1, for excision of damaged bases from DNA exposed to gamma-irradiation. Excision products were identified and quantified using gas chromatography/isotope dilution mass spectrometry (GC/IDMS). The GST-alpha-hOgg1 protein used in this study is a fusion of alpha-hOgg1 to the C-terminus of the GST protein. The results show that GST-alpha-hOgg1 protein excises 8-hydroxyguanine (8-OH-Gua) and 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua) from DNA exposed to gamma-irradiation in a solution saturated with N(2)O or air. Fourteen other lesions, including oxidised purines and pyrimidines, were not excised from these substrates. Catalytic constants were measured for the excision of 8-OH-Gua and FapyGua from DNA gamma-irradiated under N(2)O. The k (cat)/ K (m)values for excision of 8-OH-Gua and FapyGua were 4.47 x 10(-5)and 8.97 x 10(-5)(min(-1)nM(-1)), respectively. The substrate specificity and the catalytic parameters of the wild-type GST-alpha-hOgg1 protein were compared to that of a polymorphic form of alpha-hOgg1 harbouring a Ser-->Cys mutation at codon 326. In the Japanese population, 47.6% of individuals possess both alleles coding for the wild-type alpha-hOgg1-Ser(326)and mutant alpha-hOgg1-Cys(326)proteins. The GST-alpha-hOgg1-Cys(326)protein was purified and its substrate specificity was determined by GC/IDMS analysis. The results show that the GST-alpha-hOgg1-Cys(326)protein efficiently excises 8-OH-Gua and FapyGua from gamma-irradiated DNA. The k (cat)/ K (m)values for excision of 8-OH-Gua and FapyGua were 2. 82 x 10(-5)and 4.43 x 10(-5)(min(-1)nM(-1)), respectively. Furthermore, we compared the capacity of these two forms of alpha-hOgg1 to act on substrates containing 2,6-diamino-4-hydroxy-5- N -methylformamidopyrimidine (Me-FapyGua). The k (cat)/ K (m)values for excision of Me-FapyGua were 278 x 10(-5)and 319 x 10(-5)(min(-1)nM(-1)), respectively. Cleavage of 34mer oligodeoxyribonucleotides containing 8-OH-Gua, 8-hydroxyadenine or an apurinic/apyrimidinic site paired with a cytosine was also investigated. The results show that both GST-alpha-hOgg1-Ser(326)and GST-alpha-hOgg1-Cys(326)catalyse the various cleavage reactions at very similar rates. Furthermore, both proteins efficiently complement the mutator phenotype of the fpg mutY mutant of Escherichia coli.